Measuring and Mending Monetary Policy Effectiveness Under Capital Account Restrictions : Lessons from Mauritania - Blotevogel, Robert (IMF Working Papers; Working Paper ;, 2013)
I propose a new approach to identifying exogenous monetary policy shocks in low-income countries with capital account restrictions. In the case of Mauritania, a domestic repatriation requirement is the key institutional characteristic that allows me to establish exogeneity. Unlike in advanced countries, I find no evidence for a statistically significant impact of exogenous monetary policy shocks on bank lending. Using a unique bank-level dataset on monthly balance sheets of six Mauritanian banks over the period 2006-11, I estimate structural vector autoregressions and two-stage least square panel models to demonstrate the ineffectiveness of monetary policy. Finally, I discuss how a reduction in banks' loan concentration ratios and improvements in the liquidity management framework could make monetary stimuli more effective.